2011
DOI: 10.1089/ten.tea.2010.0714
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tissue Engineering with Decellularized Rhesus Monkey Kidneys: Age-Related Differences

Abstract: New therapies for severely damaged kidneys are needed due to limited regenerative capacity and organ donor shortages. The goal of this study was to repopulate decellularized kidney sections in vitro and to determine the impact of donor age on recellularization. This was addressed by generating decellularized kidney scaffolds from fetal, juvenile, and adult rhesus monkey kidney sections using a procedure that removes cellular components while preserving the structural and functional properties of the native ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 36 publications
(46 reference statements)
0
44
0
Order By: Relevance
“…growth factors, cytokines and proteases), we developed a decellularization protocol allowing parallel decellularization of whole fetal hearts and adult LV explants, while assuring a reliable comparison between both microenvironments by eliminating differences inherent to the use of distinct procedures. The decellularization of adult organs, in contrast to fetal tissues [20,46,47], has been extensively reported [6,10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…growth factors, cytokines and proteases), we developed a decellularization protocol allowing parallel decellularization of whole fetal hearts and adult LV explants, while assuring a reliable comparison between both microenvironments by eliminating differences inherent to the use of distinct procedures. The decellularization of adult organs, in contrast to fetal tissues [20,46,47], has been extensively reported [6,10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…17,44 A comparison of decellularized organ scaffolds found that fetal and juvenile (3 months old to 1.5 y old) rhesus monkey kidney DECM allowed greater organ repopulation and tubular structure formation than adult (5-13 y old) DECM. 45 Choi and colleagues found that DECM produced by young cells restored a youthful phenotype to senescent human fibroblasts, resulting in an additional 25 population doublings (a 39% increase in cellular lifespan). 46 This finding was applied to female mouse (C57BL/6) BMSCs by Sun and colleagues, who reported that the defective replication of aged (18 months old) BMSCs was reversed by exposure to DECM from young (3 months old) animals.…”
Section: Rejuvenation Of Elderly Cells By Young Ecmmentioning
confidence: 99%
“…This interesting article compares the differentiation of HES toward kidney and lung lineages when HES are grown on decellularized kidney and lung slices. The thickness of the slices is not mentioned in this article (or in an earlier article by the same group 35 ), but they appear to be around 2-3 mm based on figure 2 of both articles. Although the matrices are shown to direct correct spatial organization of the cells, overall expression of kidney-and lung-associated markers was not statistically different.…”
Section: Discussionmentioning
confidence: 70%